Tiktok Dalam Cultural Studies Dan Media - Ananta, Pinka Erly (Universitas Nahdlatul Ulama Blitar, 2023)
TikTok, as a popular social media platform in Indonesia, has been the subject of attention in several studies related to national culture and identity. In relation to cultural studies, TikTok can be seen as an example of how modern communication technologies influence people's culture and identity. In several studies, TikTok has been found to have a significant influence on Indonesian culture, both directly and indirectly. In synthesis, TikTok in cultural studies and media can be seen as an example of how modern communication technology influences people's culture and identity. TikTok has been instrumental in influencing Indonesian culture, both directly and indirectly, and has become an effective platform to promote Indonesian culture and culture.